1996
DOI: 10.1002/j.1460-2075.1996.tb01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus latent membrane protein (LMP1) is not sufficient to maintain proliferation of B cells but both it and activated CD40 can prolong their survival.

Abstract: Epstein‐Barr virus (EBV) infects human primary B lymphocytes and induces and maintains proliferation of these cells efficiently in vitro. Mutants of Epstein‐Barr virus which express EBV nuclear antigen 2 (EBNA2) in a conditional fashion allow dissection of individual contributions of viral genes to B cell immortalization. EBNA2 is a transcriptional activator of cellular and viral genes, including the viral latent membrane protein 1 (LMP1), which is essential for B cell immortalization and has oncogenic effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 59 publications
3
89
0
1
Order By: Relevance
“…The proliferation induced by IL-10 in the absence of EBNA-2 in the ER/EB2-5 cells is intriguing since ectopic expression of LMP-1 in the ER/EB2-5 cells could not maintain the proliferation of these cells. 49 Furthermore IL-10 alone did not induce the proliferation of normal B cells but strongly enhanced proliferation when combined with CD40 or BCR activation. 50 Since LMP-1 mimics a constitutively active CD40 receptor, IL-10 together with LMP-1 might drive the cells into the cell cycle.…”
Section: Discussionmentioning
confidence: 93%
“…The proliferation induced by IL-10 in the absence of EBNA-2 in the ER/EB2-5 cells is intriguing since ectopic expression of LMP-1 in the ER/EB2-5 cells could not maintain the proliferation of these cells. 49 Furthermore IL-10 alone did not induce the proliferation of normal B cells but strongly enhanced proliferation when combined with CD40 or BCR activation. 50 Since LMP-1 mimics a constitutively active CD40 receptor, IL-10 together with LMP-1 might drive the cells into the cell cycle.…”
Section: Discussionmentioning
confidence: 93%
“…In an LCL established with an EBV recombinant in which EBNA2 and LMP1 expression can be silenced, both are required for continuous proliferation and protection from apoptosis. Importantly, LMP1 expression in trans or CD40 engagement can prolong cell survival in these cells (Zimber-Strobl et al, 1996). LMP1 can also protect cells from serum starvation-, etoposide-, and p53-induced apoptosis (Fries et al, 1996;Kawanishi, 1997;Kenney et al, 1998).…”
Section: Lmp1 Protects Cells From Apoptosismentioning
confidence: 99%
“…A previous report showed that CD40 induced the production of interleukin-10 at a low dose and induced the secretion of interleukin-12 at a high dose [23]. Our previous research also showed that CD40 antibody stimulated MM cell proliferation at a low dose but induced the apoptosis of myeloma cells at a high dose [24,25]. Therefore, the infected cells may be regulated through CD40L upregulation and CD40 downregulation such that a favorable signal intensity is reached to regulate cell growth.…”
Section: Figurementioning
confidence: 72%